Variaciones en las pautas de localización industrial formación del "Corredor Industrial del Ebro" y General Motors - Alonso Logroño, María Pilar (Geographicalia, 2017)
The work revises in what manners the location of the factory General Motors E., 30 kilometres far from the city centre of Zaragoza, is helping to the remalk of two aspects: the research of a new industrial setting far from the city this due to the new and more advanced means of transport and on the other hand the consolidatione of "Corredor Industrial del Ebro" live one of the most dinamic and working areas into the Ebro net work.